2022
DOI: 10.3389/fnins.2022.917071
|View full text |Cite
|
Sign up to set email alerts
|

Ascl1 phospho-site mutations enhance neuronal conversion of adult cortical astrocytes in vivo

Abstract: Direct neuronal reprogramming, the process whereby a terminally differentiated cell is converted into an induced neuron without traversing a pluripotent state, has tremendous therapeutic potential for a host of neurodegenerative diseases. While there is strong evidence for astrocyte-to-neuron conversion in vitro, in vivo studies in the adult brain are less supportive or controversial. Here, we set out to enhance the efficacy of neuronal conversion of adult astrocytes in vivo by optimizing the neurogenic capaci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 70 publications
(144 reference statements)
0
6
0
Order By: Relevance
“…We and others found that proneural transcription factors are inhibited by phosphorylation in embryonic mouse brain and spinal cord, in Xenopus and fruit fly primary neurogenesis, and in cancer cells (Ali et al, 2011; Ali et al, 2020; Azzarelli et al, 2015; Azzarelli et al, 2022; Ge et al, 2006; Hand et al, 2005; Hindley et al, 2012; Li et al, 2014; Li et al, 2012; Quan et al, 2016; Sun et al, 2001). We used this knowledge to mutate Ascl1 so that it cannot be phosphorylated and remains active, and showed that this designer proneural transcription factor is more efficient at lineage conversion of an astrocyte to an induced neuron than native Ascl1 (Ghazale et al, 2022). In this study, we used a similar strategy to mutate SP and TP sites in Neurog2 to generate Neurog2 SA9TA1 , and we demonstrated that this mutated version has an enhanced capacity to transactivate known Neurog2 target genes, Ppp1r17 and Col3a1.…”
Section: Discussionmentioning
confidence: 99%
“…We and others found that proneural transcription factors are inhibited by phosphorylation in embryonic mouse brain and spinal cord, in Xenopus and fruit fly primary neurogenesis, and in cancer cells (Ali et al, 2011; Ali et al, 2020; Azzarelli et al, 2015; Azzarelli et al, 2022; Ge et al, 2006; Hand et al, 2005; Hindley et al, 2012; Li et al, 2014; Li et al, 2012; Quan et al, 2016; Sun et al, 2001). We used this knowledge to mutate Ascl1 so that it cannot be phosphorylated and remains active, and showed that this designer proneural transcription factor is more efficient at lineage conversion of an astrocyte to an induced neuron than native Ascl1 (Ghazale et al, 2022). In this study, we used a similar strategy to mutate SP and TP sites in Neurog2 to generate Neurog2 SA9TA1 , and we demonstrated that this mutated version has an enhanced capacity to transactivate known Neurog2 target genes, Ppp1r17 and Col3a1.…”
Section: Discussionmentioning
confidence: 99%
“…Among the targets of ASCL1, Klf10 is involved in neuritogenesis of iN cells in the early stage, Myt1 and Myt1l are critical for the electrophysiological maturation of iN cells, and Neurod4 and Chd7 are required for the efficient conversion of astrocytes into neurons ( Rao Z. et al, 2021 ). Another study found that mutating six serine phosphorylation receptor sites in Ascl1 to Ascl1 SA6 could enhance the conversion of astrocytes into neurons in the mouse cerebral cortex ( Ghazale et al, 2022 ). Giehrl-Schwab et al (2022) developed the AAV-based intronic peptide split dcas9 activator system (AAV DCAS) by delivering Ascl1, Lmx1a NeuroD1, Lmx1a, Nr4a2 (ALN)/Ascl1, and miRNA218 (ALNe-218) in various combinations to efficiently reprogram striatal astrocytes into GABAergic neurons and integrate them into neural circuits, thereby improving voluntary motor function in a 6-OHDA-induced PD mouse model.…”
Section: In Vivo Reprogramming Of Astrocytes or Glia Into Ne...mentioning
confidence: 99%
“…Ghazale et al. mutated proneural gene Asc11 by mutating 6 serine prospho-acceptor sites (Asc11 SA6 ), which was found to enhance reprogramming and downregulate astrocytic markers such as Sox9 and GFAP [124] .…”
Section: Promoting Regeneration After Scimentioning
confidence: 99%